PENGARUH MODEL PEMBELAJARAN DAN GAYA MENGAJAR GURU TEHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PKN - Muh Hadiatur Rahman (Jurnal Penelitian dan Pendidikan IPS, 2016)
Learning Achievement (2) know the teacher’s teaching styleToward Students’ Learning Achievement (3) know the instructional model and The teacher’s teaching style simultaneously Toward Students’ Learning Achievement for tenth grade at Vocational High School 3 Pamekasan Regency.The design of this research is quantitative to know the influence of independents variabels to dependent variable. The method of data collection of this research used questionnaires dan documentation. The population  of this research is tenth grade students at Vocational High School 3 Pamekasan Regency. the number students as sample 70 (0%). The technique of data analyze used regression and ANOVA to measure learning achievement and the coeffecient correlation between vareabels. The result can be shown as the following: The instructional model  gave influently significant toward students’ learning avhievement. It was shown that hyphotesis test of t-account 0,595 which is lesser than t-table about 3,11 in the significant level 0,05 and teacher’s teaching style gave influently significant toward students’ learning avhievement. It was shown that hyphotesis test of t-account 0,463 which is lesser than t-table about 3,11 in the significant level 0,05. There was a correlation between instructional model and the teacher’s teaching style toward students’ learning achievement simultaneously. It was shown on the result of ANOVA analysis by getting F-account about 0,293 that means is higher than F-table about = 3,11 it means that f-table is about = 3,11 in the significant level 0,05.